Analysis of suckler cow reproductive performance and its contribution to financial performance on Irish beef farms. (3rd October 2017) - Taylor, R. F.; McGee, M.; Crosson, P.; Kelly, A. K.
Abstract : The aim of this study was to analyse cow reproductive performance on 37 Irish suckler beef farms and determine how reproductive efficiency influences farm profitability. The main reproductive factors associated with gross output value per livestock unit (GO/LU) were average age at first calving ( r =−0.19, P <0.01) and number of months with a calving ( r =−0.15, P <0.05). A 1 month increase in average age at first calving was shown to reduce GO/LU by €14 across suckler farms. Average age at first calving was positively correlated with calving interval ( r =0.21, P <0.001) and the number of months with a calving ( r =0.18, P <0.01). Number of months with a calving was also positively correlated with calf mortality ( r =0.21, P <0.01). However, these relationships between reproductive variables had no statistically significant impact on farm financial performance. It is therefore concluded that additional analysis at animal level is required to determine key reproductive indicators contributing to farm profitability.